Novel Mutations in gB and gH Circumvent the Requirement for Known gD Receptors in Herpes Simplex Virus 1 Entry and Cell-to-Cell Spread - Uchida, Hiroaki (American Society for Microbiology, 2013)
Both entry and cell-to-cell spread of herpes simplex virus (HSV) involve a cascade of cooperative interactions among the essential glycoproteins D, B, and H/L (gD, gB, and gH/gL, respectively) initiated by the binding of gD to a cognate HSV entry receptor. We previously reported that a variant (D285N/A549T) of glycoprotein B (gB:NT) enabled primary virus entry into cells that were devoid of typical HSV entry receptors. Here, we compared the activities of the gB:NT variant with those of a newly selected variant of glycoprotein H (gH:KV) and a frequently coselected gB variant (gB:S668N). In combination, gH:KV and gB:S668N enabled primary virus entry into cells that lacked established HSV entry receptors as efficiently as did gB:NT, but separately, each variant enabled only limited entry. Remarkably, gH:KV uniquely facilitated secondary virus spread between cells that lacked canonical entry receptors. Transient expression of the four essential entry glycoproteins revealed that gH:KV, but not gB:NT, induced fusion between cells lacking the standard receptors. Because the involvement of gD remained essential for virus spread and cell fusion, we propose that gH:KV mimics a transition state of gH that responds efficiently to weak signals from gD to reach the active state. Computational modeling of the structures of wild-type gH and gH:KV revealed relatively subtle differences that may have accounted for our experimental findings. Our study shows that (i) the dependence of HSV-1 entry and spread on specific gD receptors can be reduced by sequence changes in the downstream effectors gB and gH, and (ii) the relative roles of gB and gH are different in entry and spread.